Synthesis of 2-Hydroxy-5-methoxy-3-alkyl-1,4-benzoquinones - WU, LIQIANG; YANG, CHUNGUANG; YANG, LIMIN (Asian Journal of Chemistry, 2010)
A short, efficient synthesis of 2-hydroxy-5-methoxy-3-alkyl-1,4- benzoquinones is described. Ultrasound-assisted Wittig reaction of alkyltriphenyl phosphonium bromides with 2-hydroxy-3,6-dimethoxybenzaldehyde in basic aqueous condition followed by reduction with Na/n-BuOH gave 3,6-dimethoxy-2-alkylphenols. Oxidation of 3,6- dimethoxy-2-alkylphenols with Fremy's salt produced 2,5-dimethoxy- 3-alkyl-1,4-benzoquinones. Selective hydrolysis with perchloric acid converted 2,5-dimethoxy-3-alkyl-1,4-benzoquinones to 2-hydroxy-5- methoxy-3-alkyl-1,4-benzoquinones.